Robust Forecast Evaluation of Expected Shortfall. (4th February 2019) - Ziegel, Johanna F; Krüger, Fabian; Jordan, Alexander; Fasciati, Fernando
Abstract: Motivated by the Basel III regulations, recent studies have considered joint forecasts of Value-at-Risk and Expected Shortfall. A large family of scoring functions can be used to evaluate forecast performance in this context. However, little intuitive or empirical guidance is currently available, which renders the choice of scoring function awkward in practice. We therefore develop graphical checks of whether one forecast method dominates another under a relevant class of scoring functions, and propose an associated hypothesis test. We illustrate these tools with simulation examples and an empirical analysis of S&P 500 and DAX returns.